2004
DOI: 10.22358/jafs/67623/2004
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and health functions of carbohydrate for pigs

Abstract: The greatest progress in carbohydrate study in pig nutrition and health is that the carbohydrates are classified more clearly not only based on their structure, but also on their nutritional functions. Carbohydrates serve as components of cell structures, energy substrate and have regulatory functions. There are large differences in the digestion, absorption and the speed of the carbohydrates appearance in the portal vein blood plasma. Non-starch polysaccharides (NSP) and particularly soluble one and resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…The inclusion of purified cellulose may have blocked adherence sites of certain pathogenic bacteria, thus immobilizing or reducing their ability to remain in the gastrointestinal tract and, consequently, resulting in their elimination with the chyme and reducing diarrhea (Schley & Field, 2002;Yin et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of purified cellulose may have blocked adherence sites of certain pathogenic bacteria, thus immobilizing or reducing their ability to remain in the gastrointestinal tract and, consequently, resulting in their elimination with the chyme and reducing diarrhea (Schley & Field, 2002;Yin et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…According to different authors [54,55], because cassava root has high moisture content (62-68%) and easily fermentable carbohydrate, it may be suitable for silage. As silage, cassava roots have high dry matter content, crude protein, crude fibre and ash [56].…”
Section: Physical Processing Of Cassava For Poultry Feedingmentioning
confidence: 99%
“…Mateos et al (2006) and Kim et al (2008) reported that adding insoluble fibre leads to a reduction in diarrhoea in weaned piglets. According to Schley and Field (2002) and Yin et al (2004), the inclusion of insoluble fibre may limit the adherence of pathogenic bacteria, immobilizing or reducing its ability to remain in the gastrointestinal tract, resulting in its elimination in the faeces and a reduction of diarrhoea. The results of this study agree with those found by Hanczakoswska, Swiatkiewicz and Bialecka (2008), who tested supplementation levels of pure cellulose in the diets of weaned piglets and verified that the addition of this source of fibre resulted in lower occurrence of diarrhoea.…”
Section: Performance and Diarrhoea Occurrencementioning
confidence: 99%
“…Thus, diets with 8.5 and 10.5% NDF may have resulted in substrate for pathogenic bacteria in the intestinal tract, causing a possible inflammatory effect of the mucosa (Karr-Lilienthal et al, 2005;Brasil et al, 2009), while the diets with more than 12.2% NDF may have had a mechanical effect, limiting the adhesion of pathogenic bacteria that, possibly, were excreted in faeces, but the abrasive effect on the gut epithelium may have caused villus atrophy with increased shedding of cells, which can even increase the excretion of nitrogen in the faeces (Schley and Field, 2002;Yin et al, 2004).…”
Section: Histological Parameters Of the Intestinal Mucosa And Morpholmentioning
confidence: 99%